COMPARATIVE LEVELS OF LIVER ENZYMES IN PATIENTS WITH VARIOUS LIVER DISORDERS - B.GAYATHRI; M.VASANTHA (International Journal of Pharma and Bio Sciences, 2015)
Hepatic injury is associated with distortion of the metabolic function. Hepatic disease can be evaluated by biochemical analysis of the serum tests, includes levels of serum Alanine and Aspartate aminotransferases, alkaline phosphatase, and others. The present study was conducted to assay Liver associated enzymes on patients with Viral Hepatitis, Alcoholic hepatitis and Chronic hepatitis and to find out the comparative levels of enzymes between the groups. In this study, total 60 subjects (15 Healthy controls and 45 patients “Case group”) aged between 18 to 60 years was enrolled. Each case group consisted of 15 patients suffering with Viral Hepatitis, Alcoholic hepatitis and Chronic hepatitis respectively. Serum levels of Alanine and As partate aminotransferases, alkaline phosphatase and Gamma glutamyle transferase were analyzed using standard methods. Comparative elevation of Liver associated enzymes was observed to indicate the degree of Hepatic Damage in Viral Hepatitis, Alcoholic hepatitis and Chronic hepatitis.